Improving Financial Management and Taxation Systems in Azzahra Bee Farm MSMEs - Agus Tina; Khana Saputri; Ninta Katharina; Wirda Lilia; Jessy Safitri Sitorus (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
Honey bee cultivation is a technique for caring for honey bee colonies that live in hives. Apart from producing honey, bee cultivation can also produce other products such as propolis, pollen and royal jelly. The honey produced by honey bees has been proven to be efficacious in maintaining body health and can treat several types of diseases. Honey bee cultivation is a very attractive alternative for the community so it can be used as a very promising business field to increase income. For this reason, knowledge of financial management and a good taxation system is needed to support the development of the honey bee cultivation business. UMKM Azzahra Bee Farm is an UMKM engaged in cultivating honey bees located on Jl. Melati Raya - I No.6 Sempakata Village, Medan Selayang District. A survey conducted by the PKM team found problems related to financial management and the tax system that were still poorly understood. So far, financial management has not been properly recorded and understanding of the tax system is still very minimal. The PKM team intends to carry out PKM activities using an approach method through counseling and workshops regarding financial management and the taxation system for MSMEs. Through this PKM activity, it is hoped that it will be beneficial for Azzahra Bee Farm MSMEs in the form of increasing knowledge and skills related to financial management and the taxation system for MSMEs.